THE EFFECT OF WORK DICIPLINE IN INCREASING EMPLOYEE PERFORMANCE AT CV DUTA BARITO BANJARMASIN - Hayati, Diana; Sylvia, Rika (Universitas Muhammadiyah Kalimantan Timur, 2022)
CV Duta Barito Banjarmasin is a company that was initially engaged in selling raw rattan products and now sells finished products. The purpose of this study was to determine the effect of work discipline on employee performance at CV Duta Barito Banjarmasin. The type of research used is descriptive quantitative, where the sample in this study are employees in the production section, totaling 30 people. Sources of data in this study are primary data and secondary data. The data collection techniques used were through questionnaires, observation, interviews, and documentation. While the data analysis method was carried out on the results of the questionnaire answers using the SPSS for Windows version 23 program. The results of the study were from the work discipline variable that affected employee work performance, where discipline was evidence of a sense of responsibility for the tasks assigned to him, so that it would also have a positive impact. against the company. Where from the calculation shows that work discipline has a positive and significant effect on employee performance with a significant value of 0.000 and less than 0.05, which means that work discipline increases, employee performance will also increase with an influence value of 60.5%.